In situ growth of graphdiyne on arbitrary substrates with a controlled-release method. Issue 47 (24th May 2018) - Zhao, Fuhua; Wang, Ning; Zhang, Mingjia; Sápi, András; Yu, Jiaojiao; Li, Xiaodong; Cui, Weiwei; Yang, Ze; Huang, Changshui
Abstract : GDY is in situ synthesized on arbitrary substrates catalyzed by Cu 2+ -ions escaping from the PVP/Cu(OAc)2 film on the surface of substrates. Abstract : A versatile controlled-release method was developed for the in situ growth of graphdiyne on arbitrary substrates. Cu 2+ -Ions escaped from the polyvinylpyrrolidone/copper acetate film on the surface of various substrates ( e.g. SiO2, ZnO, Al, etc. ), acting as the catalyst for the acetylenic coupling reaction.